THE PRINCIPLES OF TIGHTENING DIVORCE IN SEMARANG HIGH RELIGIOUS COURT IN MAQASID AL-SHARIâAH PERSPECTIVE - Hasyim, A. Muliany (Al-Mawarid Jurnal Hukum Islam, 2015)
The following article is the result of the authorâs study (dissertation) which focus the need to tighten the divorce because the marriage is very strong agreement that aims to create a happy home and eternal, sakinah mawaddah and mercy, suppress escalation of divorce while reducing the negative impact on children after divorce her parents. The location of the study authors are in the jurisdiction of PTA Semarang. These results indicate that Semarang PTA in examining divorce case has been applying the principles of tightening divorce, mediation institutions maximize and optimize Hakam institutions to realize the goal of marriage, if successful peace revoked case, if it turns out there is no reason the case is not accepted, if it can not prove the case rejected , If proven, there is reason enough divorce, unsuccessful peace efforts and apply the theory of benefit, as the central idea Maqasid al-Shariah, divorce is granted by refusing mafsadah more important consideration than grabbing maslahah mafsadah refused because it is a benefit in accordance with Maqasid al-Shariah. According to the author that another attempt to tighten a divorce is necessary premarital education provision by the Religious Affairs Office (KUA) presenting the subject matter of the rights and obligations of husband and wife as well as the consequences if left malpractice. In addition, the need for regulations that provide its jurisdiction in a particular case examination and decide divorce cases the reason of domestic violence as well examining the actions of domestic violence so that the subject is no longer a litigant in two of the judiciary, in order to realize the principle is simple, fast and low cost. Keywords : Semarang PTA, Tighten, Divorce, Maqasid Shariâah and Premarital Education.